„Terrifyingly Expressionless Face of the Nubian Askari”: The Character of the German Colonial Soldier in the Novel "Afterlives" by Abdulrazak Gurnah - Nataša P. Rakić (Etnoantropološki Problemi)
Based on the analysis of Abdulrazak Gurnah's novel Afterlives, in conjunction with selected historical sources, the character of the German colonial soldier—askari—and his role in maintaining the colonial power of the German Empire is examined in this paper. From portrayals of voluntary enlistment in the colonial troops, driven by fantasies of the colonizer, to forced recruitment involving mechanisms such as abduction and coercion, Gurnah emphasizes that loyalty to the German Emperor was a common trait among all askari troops, demonstrated by their willingness to carry out assigned orders. By weaving together parallel narratives of Ilyas and Hamza, two askaris, Gurnah’s novel highlights the often overlooked colonial past of the East African coast, making a significant contribution to the (re)shaping of cultural memory of this period in German colonial history. He raises questions about postcolonial Germany’s confrontation with its colonial legacy, the revival of the idea of re-colonizing Africa during the rise of Nazism in Germany, the status of Africans in Germany between the wars and after World War II, while simultaneously revealing the difficulties surrounding war reparations for African soldiers who fought for Germany. Gurnah also emphasizes the challenging circumstances of researching Germany's colonial past, primarily caused by the lack of written sources.Through Hamza’s story, Gurnah uncovers the internal structure of the askari troops, patterns of behavior, military culture, perceptions of colonial conflicts, and warrior methods, highlighting the internal divisions, problems, and traumas that many askari soldiers faced after their service ended.